1951
DOI: 10.1002/jsfa.2740020105
|View full text |Cite
|
Sign up to set email alerts
|

The pectase activity of apples

Abstract: knowledge the control of ventilation is largely empirical, and although this may be satisfactory for certain shapes and sizes of stock of which experience exists, the more general application of this method of control depends upon a detailed study of the subject. Fig. 6 resembles Fig. 5 in lay-out but refers instead to a 2-m. column of bag material impregnated with palm-kernel fat. A general comparison of the two Figures shows that the shorter column of bag material has a heating tendency of the same order as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
1

Year Published

1959
1959
1996
1996

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 6 publications
0
12
1
1
Order By: Relevance
“…These authors also found PE activity extended over a broader pH range, especially to more acidic pH, i.e. pH 4.5 (Pollard & Kieser, 1951;Lee & Wiley, 1970). However, these workers used an extracted PE preparation, i.e.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…These authors also found PE activity extended over a broader pH range, especially to more acidic pH, i.e. pH 4.5 (Pollard & Kieser, 1951;Lee & Wiley, 1970). However, these workers used an extracted PE preparation, i.e.…”
Section: Resultsmentioning
confidence: 92%
“…3), above which there was a rapid drop in activity to inactivation at 70°C for sample A, 80°C for sample C and 90°C for sample B. Pollard & Kieser (1951) found a much more rapid drop in activity, to below 10% after 1 min, in a purified enzyme preparation heated at 68°C and over a pH range 3.5-6.0. However, when apple juice was heated under the same conditions the heat stability of PE was greatly enhanced, with juice from Laxton's Superb retaining over 80% and Blenheim Orange nearly 60% of the initial PE activity after 20min.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations